Burials and society in late Chalcolithic and Early Bronze Age Ireland - McSparron, Cormac, (Queen's University Belfast Irish archaeological monograph ;, 2020)
This text describes and analyses the increasing complexity of later Chalcolithic and Early Bronze Age burial in Ireland, using burial complexity as a proxy for increasing social complexity, and as a tool for examining social structure.